EDUCATION OF REFLECTIVE SKILLS IN FUTURE TEACHERS AS A PSYCHOLOGICAL AND PEDAGOGICAL PROBLEM (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the different scientists' views to investigating problem, specifice the content of the concept "reflexive skills".
Keywords: reflection; reflexive skills; self-education; self-dependent work; educational process